PKM tentang Pendekatan dan Tantangan Manajemen Pendidikan Islam di MTs Al Khoiriyah Putukrejo Gondanglegi Malang - Moch. Sahril Sobirin; Muhammad Husni (Indo Publishing, 2026)
Islamic Education Management is the process of managing educational institutions based on Islamic values ​​to achieve educational goals effectively and efficiently. This management encompasses the planning, organizing, implementing, supervising, and evaluating of all educational resources, including human resources, infrastructure, curriculum, and funding. The implementation of Islamic education management is not only oriented towards academic achievement, but also towards character building, noble morals, and strengthening Islamic values ​​in students. Through professional, transparent, and accountable management, Islamic educational institutions are expected to improve the quality of education and produce graduates who are knowledgeable, faithful, and pious, and able to contribute positively to community life. Thus, Islamic education management plays a strategic role in realizing national and Islamic education goals in an integrated manner.